2020
DOI: 10.1126/sciadv.aax9324
|View full text |Cite
|
Sign up to set email alerts
|

Inverse design of porous materials using artificial neural networks

Abstract: Generating optimal nanomaterials using artificial neural networks can potentially lead to a notable revolution in future materials design. Although progress has been made in creating small and simple molecules, complex materials such as crystalline porous materials have yet to be generated using any of the neural networks. Here, we have implemented a generative adversarial network that uses a training set of 31,713 known zeolites to produce 121 crystalline porous materials. Our neural network takes in inputs i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
166
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(167 citation statements)
references
References 34 publications
0
166
0
1
Order By: Relevance
“…They can aid experiments in screening possible synthetic routes and suggesting the most affordable and efficient means. For example, inverse design, a technique predicting compositions and structures of starting materials based on end-of-use functions 15 , can accelerate the discovery of novel porous organic materials.…”
Section: Emerging Materials Development By Computation and Data Scienmentioning
confidence: 99%
“…They can aid experiments in screening possible synthetic routes and suggesting the most affordable and efficient means. For example, inverse design, a technique predicting compositions and structures of starting materials based on end-of-use functions 15 , can accelerate the discovery of novel porous organic materials.…”
Section: Emerging Materials Development By Computation and Data Scienmentioning
confidence: 99%
“…Kim and co-workers started building GANs that can generate energy grids of zeolites 546 and recently extended their model to predict the structure of all-silica zeolites. 434 To do so, they used a separate channel (as is used for the RGB channels in color images) for oxygen and silicon atom positions which they encoded by placing Gaussian at the atom positions. By adjusting the loss function to target structures with a specific heat of adsorption, they could observe a drastic shift in the shape of the distribution of this property but not in the one for the void fraction or the Henry coefficient ( Figure 47 ).…”
Section: Applications Of Supervised Machine Learningmentioning
confidence: 99%
“… Distribution of Henry coefficient, void fraction and heat of adsorption for generated structures with a user-defined target range of 18–22 kJ mol –1 for the heat of adsorption. Reproduced from ref ( 434 ). …”
Section: Applications Of Supervised Machine Learningmentioning
confidence: 99%
“…There are so far no clear examples of the application of this approach to nanomaterials. In related fields, Kim et al recently reported the use of GANs in the inverse design of porous materials [68] and So and Rho used deep convolutional GANs to generate new nanophotonic structures by inverse design. [69] Gomez-Bombarelli et al showed how a DNN and a recurrent neural network (RNN) can be used as an encoder and the decoder, respectively, for inverse design.…”
Section: Inverse Designmentioning
confidence: 99%